2018
DOI: 10.1080/02701960.2018.1489249
|View full text |Cite
|
Sign up to set email alerts
|

Improving undergraduate competence in multicultural gerontology practice with fresh pedagogies: A digital storytelling case example

Abstract: Building on a student-led digital storytelling project, the author suggests that expanding definitions of two core constructs of social work education and practice, experiential learning and cultural competence, can improve outcomes for diverse older clients by increasing competence in multicultural gerontology practice. Using a variety of media, digital storytelling focuses on stories that are not often heard, like those of diverse older adults. Student-led projects provide opportunities for students to engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…They also participated in a digital life history project [2,3,10,25,30] to share their family roots and traditions with future generations. Students [2][3][4]10,23,25] and spouses [23,25,30,31,35] who accompanied older adults in these tasks, and the older adults themselves, reported a greater sense of belonging and strengthened relationships [2][3][4]10] after performing the tasks. The social associations among the participating students improved [25].…”
Section: Meaningful Community Connectionmentioning
confidence: 99%
See 4 more Smart Citations
“…They also participated in a digital life history project [2,3,10,25,30] to share their family roots and traditions with future generations. Students [2][3][4]10,23,25] and spouses [23,25,30,31,35] who accompanied older adults in these tasks, and the older adults themselves, reported a greater sense of belonging and strengthened relationships [2][3][4]10] after performing the tasks. The social associations among the participating students improved [25].…”
Section: Meaningful Community Connectionmentioning
confidence: 99%
“…Older adults shared stories through DST with families, young people, and caregivers. After attending DST exhibitions, many community residents reported that they better understood and connected with the older adults [2][3][4]10,11,[23][24][25][32][33][34].…”
Section: Themesmentioning
confidence: 99%
See 3 more Smart Citations